Hyperprogressive Disease in Malignant Carcinoma With Immune Checkpoint Inhibitor Use: A Review - Liu, Xiaojun; Qiao, Liang (Frontiers in Nutrition, 2022)
Immune checkpoint inhibitors (ICIs) have shown durable remissions and improved long-term survival across a variety of cancer types. However, there is growing evidence that a significant subset of nonresponsive patients may exhibit hyperprogressive disease (HPD) during the initiation of immune checkpoint inhibitors (ICIs). Moreover, patients of HPD triggered by immune checkpoint inhibitors are always correlated with deteriorating quality of life and poor prognosis. The ability to predict such rapid disease progression phenotypes are of great importance. More precision parameters to evaluate the response pattern to ICIs is urgently needed. To date, the mechanisms of HPD are still unclear. Aberrant alterations of driven genes, tumor microenvironment or T cell immunophenotype may involve in HPD. In this work, we aim to provide an updated overview of available studies on HPD, summarize the potential predictors associated to HPD and the underly mechanisms of HPD.